Pros and pitfalls of externalized trans-anastomotic stent as a mitigation strategy of POPF: a prospective risk-stratified observational series. Issue 7 (July 2021) - Andrianello, Stefano; Marchegiani, Giovanni; Balduzzi, Alberto; Bastin, Alessandro; Masini, Gaia; Esposito, Alessandro; Casetti, Luca; Bassi, Claudio; Salvia, Roberto
Abstract: Background : Several advantages and pitfalls have been related to externalized trans-anastomotic stents (ETS) after pancreaticoduodenectomy. The purpose of this study was to investigate the effect of an ETS effect in a risk-stratified setting. Methods: Data from patients at either intermediate- or high-risk for postoperative pancreatic fistula (POPF) following pancreaticoduodenectomy were prospectively analyzed from January 2016 to December 2019. Outcomes included POPF rate, mean complication burden (ACB), and complications related to ETS malfunction. Results: A total of 540 patients met the inclusion criteria. Following an intention-to-treat analysis, there was no difference in terms of POPF and the ACB in the intermediate (22 vs.29%, p = 0.148; 0.38 vs.0.24, p = 0.082) and high-risk categories (58 vs.37%, p = 0.103; 0.33 vs.0.33, p = 0.478) comparing PJ to PJ-ETS. Excluding patients experiencing ETS malfunction (n = 45, 22%), ETS was associated with a significantly reduced ACB in the intermediate-risk (0.38 vs.0.26, p = 0.009) and POPF rate in the high-risk category (58 vs.32%, p = 0.033). In patients with ETS malfunction an increased rate of severe morbidity (Clavien-Dindo ≥ III, 33 vs.19%, p = 0.044) was observed as compared to patients with functioning ETS. Conclusion: ETS provides crucial advantages for prevention and mitigation of POPF depending on risk setting and its correct functioning. ETS malfunction is not uncommon and increases morbidity. Improving ETS design and fixing technique might lead to better outcomes.